The Intricacies of Workplace Territoriality: An Exploratory Study on the Phenomenon of Desk Appropriation in Organizational Settings - Tjahjana, Dominicus Josephus Swanto; Rusilawati, Ermina; Andi, Andi; Mitchell, Lorraine; MacDonald, Ethan; Thompson, Laura; O'Connor, Mary (Nexus Synergy: A Business Perspective, 2023)
This research delves into the intricate phenomenon of desk appropriation within workplace settings, guided by Human Resource Management (HRM) principles. Employing a mixed-methods approach, the study combines qualitative and quantitative methodologies to comprehensively explore the prevalence, underlying dynamics, and impact of desk appropriation. Across diverse industries and organizational levels, instances of desk appropriation prove noteworthy, influenced significantly by power dynamics and office politics, involving both managerial perpetration and victimhood. The psychological repercussions on affected individuals manifest in heightened stress and diminished job satisfaction, emphasizing implications for employee well-being. The study underscores the adverse effects of desk appropriation on teamwork, collaboration, and overall organizational culture. Employee coping mechanisms, including seeking social support and workspace modifications, emerge alongside organizational responses featuring clear policies and prompt resolutions. Recommendations for HRM practices emphasize the development of precise workspace etiquette policies, targeted training programs, and robust organizational support mechanisms. Contributing practical insights to HRM, this research aims to guide organizations in fostering inclusive, collaborative, and supportive workplace environments. Acknowledging limitations and paving the way for future research, the findings aspire to inform HRM practitioners and organizational leaders, promoting workplaces that prioritize employee well-being, collaboration, and a positive organizational culture.